Selective near-infrared (NIR) photodetectors fabricated with colloidal CdS:Co quantum dots - Maity P.; Singh S.V.; Biring S.; Pal B.N.; Ghosh A.K. (My University, 2025)
Herein, cobalt-doped cadmium sulphide CdS (CdS:Co) quantum dots (QDs) were synthesized by an organometallic synthesis route using different doping concentrations of Co ranging from 1 to 8%. Optical absorption data indicate the appearance of a new NIR absorption peak of the QDs due to Co doping; moreover, the intensity of the peak increases with the doping concentration; this NIR absorption peak originates from the existence of a doping band located in close vicinity to the valence band inside the band gap. The electrical conductivities of the CdS:Co thin films 'in the dark' show increasing conductivity with doping concentration; this supports the enhancement of the carrier concentration in the valence/conduction band. In addition to the dark current, the photosensitivities of these CdS:Co QDs thin film increase gradually with doping, and significant enhancement was observed in the zinc oxide (ZnO) CdS:Co QD heterojunction structure. Lateral ZnO/CdS:Co heterojunction photodetectors with different doping concentrations of Co2+ show selective NIR sensitivity, which is not realized in the case of undoped CdS. The highest detectivity was observed for the 8% doped CdS:Co heterojunction photodetector, with the detectivity of 3.1 × 1011 Jones with illumination of 820 nm wavelength light under 5.0 V external bias, which is significantly high for an NIR photodetector. © 2019 The Royal Society of Chemistry.